2022
DOI: 10.3389/fmars.2022.884715
|View full text |Cite
|
Sign up to set email alerts
|

Spotlighting Women-Led Fisheries Livelihoods Toward Sustainable Coastal Governance: The Estuarine and Mangrove Ecosystem Shellfisheries of West Africa

Abstract: The governance of coastal and marine resources remains a complex socio-ecological endeavor in many African countries, but women are leading the way and demonstrating a pathway for food fish security through rights-based co-management of shellfisheries in estuarine and mangrove ecosystems in West Africa. We report comprehensively, for the first time, the scale of estuarine and mangrove ecosystem-based shellfisheries across the West African coast (Senegal, Gambia, Guinea Bissau, Guinea, Sierra Leone, Liberia, Cô… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The collection of gender-disaggregated data enables SSF research to challenge assumptions about the roles of all genders. For example, a recent study of West African shellfisheries found that women not only play a significant role as processors and traders, as is largely discussed in the literature, but also as harvesters (Chuku et al, 2022).…”
Section: Gender-disaggregated Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The collection of gender-disaggregated data enables SSF research to challenge assumptions about the roles of all genders. For example, a recent study of West African shellfisheries found that women not only play a significant role as processors and traders, as is largely discussed in the literature, but also as harvesters (Chuku et al, 2022).…”
Section: Gender-disaggregated Datamentioning
confidence: 99%
“…Research has shown that progress on recognitional and procedural gender equity can yield policies and interventions that are more effective and improve the sector for all actors (Galappaththi et al., 2022). For instance, women's participation in the governance of West African shellfisheries has resulted in successful user‐led co‐management that improves resource sustainability (Chuku et al., 2022). Despite these benefits, women and other gender minorities continue to be underrepresented in SSF governance and decision‐making (Fisk et al., 2023; Galappaththi et al., 2022; Kleiber et al., 2015; Pedroza‐Gutiérrez & Hapke, 2022).…”
Section: An Agenda For Gender Research In Small‐scale Fisheriesmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be ascribed to low interest and investment on the part of African governments and private sectors as well as researchers when it comes to the development and culture of the resource, although shellfish production has great potential to contribute to food and nutritional security, livelihoods, and employments. According to a recent regional study on the evaluation of coastal shellfisheries covering eleven (11) West African countries, more than 300,000 mt of shellfish were landed annually, with an appraised value of USD 336 million [2]. With the appropriate policy and enforcement interventions from regional and national fishery bodies, the yield of these fisheries could be optimized to meet the growing demand of fish.…”
Section: Introductionmentioning
confidence: 99%
“…Crassostrea gasar ), is the most exploited estuarine shellfish along the coast of West Africa (Chuku, Effah, et al., 2022; Yankson, 2004). The fishery of the oyster and other estuarine shellfish was valued at about US$300 million in 2021 alone (Chuku, Effah, et al., 2022). The meat of the oyster is a cheap source of animal protein, and the oyster trade provides a livelihood for the vulnerable in communities (women and children).…”
Section: Introductionmentioning
confidence: 99%